Arctic Offshore Oil in Russia: Optimism, Pessimism, Realism - N. N. Poussenkova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
A strong global interest in the hydrocarbon resources of the Arctic emerged in the mid-2000s, after the US Geological Survey published data on its petroleum potential. While oil prices were rising, an “Arctic optimism” prevailed everywhere, and it was anticipated that a broad-scale oil production in the Arctic would soon begin. At that time, a political aspect dominated in the Russian plans to develop Arctic offshore. Russia intended to prove that it was an energy power capable of establishing a new petroleum province in the Polar seas to replace the aging West Siberia. But later the global energy sector underwent radical changes, and optimism was gradually replaced by realism. The decline of oil prices and introduction of anti-Russian sanctions contributed to the downgrading of the Arctic plans in Russia. Besides, the monopoly of Gazprom and Rosneft over the Arctic shelf hinders the development of its hydrocarbon resources because the state companies do not have sufficient competencies to operate offshore fields on their own. After 2014, Russian oil companies began to revise downwards their plans of oil production in the Arctic seas. Given the sanctions and low oil prices, now relevant ministries also more realistically perceive the prospects of the northern continental shelf development, and their new attitude is clearly visible in their public statements. Thus, they indirectly admit that Russia is not ready yet for environmentally sustainable activities in the Arctic offshore. Actually, many experts and oil companies previously demonstrated a cautious approach to the possibility of the broad-scale oil production in the Polar seas reminding that the potential of the mature Russian oil provinces onshore is still significant. Now, the government makes a strong focus on the onshore alternatives to the Arctic shelf of Russia: the development of hard-torecover reserves, enhanced oil recovery, and support of small and mid-size companies, i.e. the priorities seemingly shift from the extensive to the intensive mode of the sector development. However, pessimistically one can recall that such plans were often made in the past and they remained on paper. Ultimately, broad-scale oil production on the Arctic continental shelf will not begin before 2035. Russian oil and shipping sectors benefit from such time-out, because they receive a chance to train qualified per sonnel capable of operating on the Arctic shelf with strict adherence to the environmental sustainability principles.